A general method to speed up fixed-parameter-tractable algorithms - Niedermeier, Rolf; Rossmanith, Peter (Information processing letters, 2000)
A fixed-parameter-tractable algorithm, or FPT algorithm for short, gets an instance (I,k) as its input and has to decide whether (I,k)∈ L for some parameterized problem L . Many parameterized algorithms work in two stages: reduction to a problem kernel and bounded search tree. Their time complexity is then of the form O(p(|I|)+q(k)ξ k) , where q(k) is the size of the problem kernel. We show how to modify these algorithms to obtain time complexity O(p(|I|)+ξ k) , if q(k) is polynomial.